Application of DNA fingerprinting to the recovery program of the endangered Puerto Rican parrot. - Brock, M K (1992)
The Puerto Rican parrot was reduced to approximately 13 animals in 1975 and as a conservation measure, a captive population was established from a few founders taken from the wild between 1973 and 1983. The number of successful breeding pairs in captivity has been low, and the captive breeding program has not been as productive as that of the closely related Hispaniolan parrot. Therefore, a genetic study was initiated to examine the relative levels of relatedness of the captive founders using levels of bandsharing in DNA fingerprints. Unrelated captive founder Puerto Rican parrots had the same average level of bandsharing (0.41) as second-degree relatives of the Hispaniolan parrot (0.38, P > 0.05), with an inbreeding coefficient of 0.04. High levels of bandsharing (> 40%) between pairs of males and females correlated with reproductive failure, suggesting that inbreeding depression is partly responsible for the low number of breeding pairs. Consequently, DNA profiling can be used to guide the captive breeding program for the Puerto Rican parrot, and other endangered species, by identifying pairs of males and females with low levels of bandsharing.